Identification and quantitative determination of arbutin in the herb of Orthilia secunda - A. V. Lezina; I. I. Terninko; M. V. Krysko (Разработка и регистрация лекарственных средств, 2021)
Introduction. Orthilia secunda (L.) House is a perennial herb that grows in Europe, Siberia, Asia Minor and Central Asia. The herb of Orthilia secunda is actively used in folk medicine as a diuretic, wound-healing and anti-inflammatory agent. From literary sources it is known that this medicinal plant raw material (PRM) contains flavonoids, tannins, organic acids, vitamins, as well as simple phenols and their derivatives (arbutin and hydroquinone). The presence of arbutin is responsible for the plant's high antioxidant and anti-inflammatory properties. But the use of Orthilia secunda in official medicine is limited due to the lack of complete information on the chemical composition and criteria for standardization of this type of medicinal product.Aim. Identification and quantification of arbutin by chromatographic methods in Orthilia secunda (L.) House, harvested in various phytocenotic zones.Materials and methods. The investigated medicinal plant material – the herb of Orthilia secunda – was harvested in various phytocenotic zones: in July 2018, harvesting was carried out in the northern part of Kazakhstan (Kokshetau district), in July-August 2019 in the Perm Territory and in the Tyumen Region. Preliminary identification of arbutin and related phenols – gallic acid and hydroquinone – was carried out by high performance thin layer chromatography (HPTLC) on a CAMAG instrument with a UV cabinet (Merck HPTLC silica gel 60 F154 plates, 20 × 10), semi-automatic Linomat 5 applicator (sample application). Elution of the plates was performed in a CAMAG Automatic Developing Chamber (ADC2). Image fixation was performed on a CAMAG Scanner 3 spectrodensitometer. The quantitative determination of arbutin was carried out by the method of highperformance liquid chromatography, which was carried out on a Prominence LC-20 device (Shimadzu, Japan) according to the validated method described in the European Pharmacopoeia 10.0. Diode array detector SPD-M20A, column Intersil C18 column (250–4.6 mm, 5 μm) (Phenomenex, USA). The results were processed using the LabSolution software. The identification and quantification of arbutin was carried out in comparison with a standard solution containing a reference sample (RS) of arbutin (C = 0,025 mg/ml) and RS of hydroquinone (C = 0,0125 mg/ml).Results and discussion. HPTLC analysis made it possible to detect arbutin and gallic acid – the main product of hydrolytic degradation/ precursor of the biosynthesis of tannins of the hydrolysable group – in the herb of Orthilia secunda from different places of growth. HPLC analysis demonstrates a different chromatographic profile of Orthilia herb harvested in different phytocenotic zones. However, in all studied objects, the absence of hydroquinone and the presence of substances that can presumably be attributed to its derivatives were confirmed, which is confirmed by the visual similarity of the spectra of these compounds and the proximity of the extrema. It was found that arbutin does not belong to the marker (majority) compounds of Orthilia. Its content is low and reaches a maximum (about 0,021 %) in the herb of Orthilia secunda growing on the territory of Kazakhstan, while in the herb of Orthilia harvested in the Perm Territory arbutin was not identified. From the data obtained, it follows that the greatest accumulation of arbutin occurs in areas with a warmer and drier climate (northern part of Kazakhstan).Conclusion. HPTLC analysis of the herb Orthilia secunda allowed the identification of arbutin and gallic acid (the main precursor of tannins of the hydrolysable group). The results of HPLC analysis of Orthilia herb harvested in various phytocenotic zones suggest quantitative differences in the content of arbutin depending on the region of growth. From the experimental data, it follows that Orthilia growing in the northern part of Kazakhstan accumulates the maximum (0,021%) amount of arbutin, in comparison with the samples harvested in the Tyumen region and the Perm region. At the same time, Orthilia harvested in the Perm Territory does not accumulate arbutin. The presence of hydroquinone has not been confirmed (by HPTLC and HPLC methods); therefore, it is not justified to talk about the hydrolytic cleavage of arbutin in the process of biosynthesis or drying. However, in all studied objects there are peaks of substances with spectral characteristics like hydroquinone, which makes it possible to assume the presence of its derivatives. Therefore, it is not advisable to position arbutin as a marker compound of Orthilia secunda harvested on the territory of the Russian Federation, and to standardize raw materials for this compound.